Multi-Similarities Bilinear Matrix Factorization-Based Method for Predicting Human Microbe–Disease Associations - Yang, Xiaoyu; Kuang, Linai; Chen, Zhiping; Wang, Lei (Frontiers in Genetics, 2021)
Accumulating studies have shown that microbes are closely related to human diseases. In this paper, a novel method called MSBMFHMDA was designed to predict potential microbe-disease associations by adopting multi-similarities bilinear matrix factorization. In MSBMFHMDA, a microbe multiple similarities matrix was constructed first based on the Gaussian interaction profile kernel similarity and cosine similarity for microbes.Then ,we use the Gaussian interaction profile kernel similarity ,cosine similarity and symptom similarity for diseases to compose the disease multiple similarities matrix .Finally ,we integrate these two similarity matrices and the microbe-disease association matrix into our model to predict potential associations . The results indicate that our method can achieve reliable AUCs of 0.9186 and 0.9043±0.0048 in the framework of leave-one-out cross validation (LOOCV) and 5-fold cross validation,respectively. what's more ,experimental results indicated that there are 10,10,8 out of the top 10 related microbes for asthma,Inflammatory bowel disease and type 2 diabetes mellitus were confirmed by experiments and literatures. Therefore,our model has favorable performance in predicting potential microbe-disease associations.